How is the discourse of the candidates adapted to the results of the surveys? (2018)
The purpose of this paper is to analyze the discourse of the candidates for Colombia’s 2018-2022 presidency and how it changes, influencing the citizens and their intention to vote. This was carried out by the follow-up of different debates and interviews, in which changes in the discourse can be found throughout the time. With the information collected, an interpretation was made in relation to the evolution of the results of the surveys of the chosen pollsters.